Rotation of the Tibial Plateau Segment to Control Arterial Haemorrhage during Tibial Plateau Levelling Osteotomy: A Cadaveric Experimental Study and Nine Clinical Cases - Roses, Leonor; Lopez de la Oliva, Paula; Arnott, Davinia (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to describe a simple and effective method to control severe haemorrhage from intraoperative trauma to the cranial tibial artery (CTA) during tibial plateau levelling osteotomy (TPLO) and to report long-term outcomes.Study Design Cadaveric descriptive study and retrospective case series. A TPLO was performed in eight cadaveric limbs, followed by intentional laceration of the CTA under fluoroscopic guidance. Dissection of the limb was performed and the relationship between the CTA and the surrounding structures was evaluated. A computed tomography angiogram was performed following TPLO in one cadaveric limb. Medical records from cases that had intraoperative arterial bleeding between 2015 and 2019 were reviewed. Cases were included if bleeding was controlled by following the usual steps for TPLO. Radiographic follow-up 6 to 10 weeks postoperatively and long-term follow-up owner's questionnaire were available.Results During TPLO, the CTA is tightly compressed between the caudal aspect of the proximal tibia and the popliteal musculature. Rotation and compression of the proximal tibia followed by closure of the pes anserinus successfully controlled arterial bleeding during TPLO in nine clinical cases without the need for direct ligation.Conclusion Continuing the usual steps of a TPLO can successfully control intraoperative bleeding from the CTA with no long-term complications. This technique should be considered in cases of arterial bleeding during TPLO before direct ligation.
Keywords: tibial plateau levelling osteotomy; cranial tibial artery; bleeding; cadaveric; angiography